Fungi as an Art Medium: The Study of the Art Medium of Philip Ross and Syaiful Aulia Garibaldi - Satrio Hari Wicaksono; Budi Irawanto; Agung Hujatnika (Journal of Urban Society's Arts, 2023)
This research aims to read the creative process carried out by bio-art artists who use fungi as a medium of character, namely Phillip Ross and Syaiful ‘Tepu’ Garibaldi and explore the potential values in their nature. New media art became an essential umbrella for non-conventional art genres related to other disciplines, such as ecology- based art, kinetic art, video art, bio-art, etc. An interdisciplinary approach that is   no longer related to a single system but a synergy between fields of science to solve increasingly complex social and environmental problems. As a new genre, bio-art synergy art and science involving organic creation components. The use of animals, viruses, fungi, and plants is the differentiator that marks the formation of bio-art works. Research methods will be conducted with methodological approaches to art history, anthropology, and semiotics. The unusual process of fungi formation used as a medium of art and ecological issues became a powerful narrative that both artists generally raised. The synergy between art, science, and technology in the creation process is a new reference in the method of art creation, especially bio-art so that  the process of fungi formation that is not commonly used as a medium of art and ecological issues related to it as a powerful narrative that the two artists generally raise becomes the main subject of study. Jamur sebagai Media Seni: Kajian Media Seni Philip Ross dan Syaiful Aulia Garibaldi. Penelitian ini bertujuan untuk membaca proses kreatif yang dilakukan oleh seniman bio-art yang memanfaatkan fungi sebagai media kekaryaannya, yaitu Phillip Ross dan Syaiful ‘Tepu’ Garibaldi serta menggali potensi nilai-nilai yang ada dalam kekaryaannya.Seni media baru menjadi payung penting untuk genre seni non- konvensional yang terkait dengan disiplin ilmu lain, seperti seni berbasis ekologi, seni kinetik, seni video, bio-art, dll. Pendekatan interdisipliner yang tidak lagi terkait dengan pendekatan tunggal tetapi sinergi antara bidang sains untuk memecahkan masalah sosial dan lingkungan yang semakin kompleks. Sebagai genre baru, bio-art adalah sinergi antara seni dan sains yang melibatkan komponen penciptaan organik. Penggunaan hewan, virus, jamur, dan tumbuhan adalah pembeda yang menandai pembentukan karya bio-seni. Metode penelitian akan dilakukan dengan pendekatan metodologi sejarah seni, antropologi, dan semiotika. Proses pembentukan fungi yang tak lazim digunakan sebagai media seni dan isu-isu ekologi yang berkaitan dengannya, menjadi narasi besar yang secara umum diangkat oleh kedua seniman tersebut. Sinergi antara seni, ilmu pengetahuan, dan teknologi dalam proses penciptaan adalah referensi baru dalam metode penciptaan seni, terutama bio-art, sehingga proses pembentukan fungi yang tak lazim digunakan sebagai media seni dan isu-isu ekologi yang berkaitan dengannya sebagai narasi besar yang secara umum diangkat oleh kedua seniman tersebut, menjadi pokok kajian utamanya.